APPLYING MELSOFT GEMINI SOFTWARE FOR DIGITAL TWIN CREATION IN AUTOMATION SYSTEM PROJECT PHASES - Thepmanee, Teerawat; Sopha, Watcharapon; Asadi, Farzin; Pongswatd, Sawai; Kummool, Sart (My University, 2026)
In the era of Industry 4.0, Digital Twin (DT) technology played a critical role in advancing manufacturing systems, particularly in real-time process simulation, performance optimization, and strategic decision-making. This study presents the application of MELSOFT Gemini software to develop DT for simulated industrial automation project phases. The system is designed to enable seamless data access and integration from physical devices into the DT in accordance with ISO 23247. The development process comprises two phases. The pre-deployment phase involves creating 3D models and simulating system behavior within a virtual environment prior to actual implementation. The Synchronized Operation phase enables visualization in MELSOFT Gemini through the transmission of data from physical devices via Operational Technology (OT) systems and Autonomous Mobile Robots (AMRs), using standard protocols such as OPC UA. The developed system accurately replicates the actual production process, provides early safety alerts, supports connectivity with various device types, and allows for future scalability all while maintaining compliance with the ISO 23247 framework. These findings demonstrate the potential of MELSOFT Gemini as a core platform for implementing practical, industry-ready DT systems.
Keywords: Automation system; Digital twin; ISO 23247; MELSOFT Gemini; Pre-deployment phase; Synchronized Operation phase